Knowledge, skills, and behavior towards chemical pesticide among vegetable growers, vegetable sellers, and consumers of Rupandehi district, Nepal - Khanal, Dipak; Neupane, Asmita; Dhital, Agrim; Paudel, Kopila; Shrestha, Madan; Upadhyaya, Navaraj (Nepalese Horticulture, 2022)
Pesticides applied on food crops and vegetables not only reduce the pest population but also leave the residue of chemicals that may result in serious health consequences. The study aims to access the knowledge, skill, and behavior towards chemical pesticides among vegetable producers, vegetable sellers, and vegetable consumers of the Rupandehi district. A survey was carried out from November 2018 to January 2019 to know the knowledge, skill, and behaviors towards chemical pesticides among vegetable growers, sellers, and consumers. The household survey was carried out with a well-designed questionnaire among 180 respondents, 60 each of vegetable producers, vegetable sellers, and vegetable consumers using the purposive sampling technique. The present study revealed that knowledge of chemical pesticides and their residue in vegetables, chemical pesticide handling skill, and behavior towards chemical pesticides among vegetable growers, sellers, and consumers was inadequate. The concerned authorities should stretch the extension services regarding pesticide use and post-use precautions to the nook and corners of Nepal as 60% of farmers seek the help of Agrovet for such information and rest either from neighbors or from manual. Sound policy formulation and implementation are necessary for judicious and rational use of chemical pesticides in vegetable crops and promoting non-chemical pest control measures. Such activities might solve pesticide-residue-related issues on the vegetable crop that makes vegetable growers, sellers, and consumers safe. Coordination among concerned organizations/agencies viz farmers group, consumers’ association and Government Organization, Non-Government Organization and International Non-Government Organization is necessary to address the issues of chemical pesticide in the vegetable supply chain.